ANALISIS KEPUTUSAN WANITA MENIKAH UNTUK BEKERJA (STUDI KASUS KOTA SURAKARTA JAWA TENGAH) - Tofelisa Sipayung, Isty Laura; Waridin, Waridin (Diponegoro Journal of Economics, 2013)
This study aimed to analyze the influence of educational variables, husbands wages, number of dependents, and age on the decision of married women to work, with a case study of Surakarta.In determining the location of the research, this study using the "multistage sampling". Next will be applied proportional sampling, the sampling in each region is proportional to the number of samples in each region. This study uses a model of "Binnary Logistic Regression", because the dependent variable is a dummy variable.Results of this study indicate that the variable levels of education, wages husband, and the number of dependents a positive influence on the decision of married women to work. While the variable age negatively affect the decision of married women to work.Â